Identifying app components that promote physical activity: a group concept mapping study - Braun,Maya; Carlier,Stéphanie; De Backere,Femke; Van De Velde,Marie; De Turck,Filip; Crombez,Geert; De Paepe,Annick L. (PeerJ, 2024)
Background Digital interventions are a promising avenue to promote physical activity in healthy adults. Current practices recommend to include end-users early on in the development process. This study focuses on the wishes and needs of users regarding an a mobile health (mHealth) application that promotes physical activity in healthy adults, and on the differences between participants who do or do not meet the World Health Organization’s recommendation of an equivalent of 150 minutes of moderate intensity physical activity. Methods We used a mixed-method design called Group Concept Mapping. In a first phase, we collected statements completing the prompt “In an app that helps me move more, I would like to see/ do/ learn the following…” during four brainstorming sessions with physically inactive individuals (n = 19). The resulting 90 statements were then sorted and rated by a new group of participants (n = 46). Sorting data was aggregated, and (dis)similarity matrices were created using multidimensional scaling. Hierarchical clustering was applied using Ward’s method. Analyses were carried out for the entire group, a subgroup of active participants and a subgroup of inactive participants. Explorative analyses further investigated ratings of the clusters as a function of activity level, gender, age and education. Results Six clusters of statements were identified, namely ‘Ease-of-use and Self-monitoring’, ‘Technical Aspects and Advertisement’, ‘Personalised Information and Support’, ‘Motivational Aspects’, ‘Goal setting, goal review and rewards’, and ‘Social Features’. The cluster ‘Ease-of-use and Self-monitoring’ was rated highest in the overall group and the active subgroup, whereas the cluster ‘Technical Aspects and Advertisement’ was scored as most relevant in the inactive subgroup. For all groups, the cluster ‘Social Features’ was scored the lowest. Explorative analysis revealed minor between-group differences. Discussion The present study identified priorities of users for an mHealth application that promotes physical activity. First, the application should be user-friendly and accessible. Second, the application should provide personalized support and information. Third, users should be able to monitor their behaviour and compare their current activity to their past performance. Fourth, users should be provided autonomy within the app, such as over which and how many notifications they would like to receive, and whether or not they want to engage with social features. These priorities can serve as guiding principles for developing mHealth applications to promote physical activity in the general population.
Keywords: Physical activity; Digital health; mhealth; ehealth; Health promotion; Group concept mapping; Mixed methods; Personalization; Participatory design